Momentum relaxation of hot electrons during radiative intraband indirect transitions in ZnS:Cr - Vlasenko, N.A.; Belyaev, A.E.; Denisova, Z.L.; Kononets, Ya.F.; Komarov, A.V.; Veligura, L.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A structureless emission in the visible region was revealed in ZnS:Cr thin-film electroluminescent structures (TFELS) apart the main near-infrared emission resulted from the 5E → 5T2 transition in the 3d shell of the Cr²⁺ ion. This emission stems from intraband indirect transitions of hot electrons. The comparison between experimental intensity spectral dependence and the same dependence calculated for different mechanisms of the momentum relaxation shows that the scattering on charged impurities takes place during this emission. The Cr+ ions existing in ZnS:Cr in addition to predominant Cr²⁺ ions serve as scattering charge centers. This is confirmed by study of the magnetic field (H) effect on the intensity (I) of the hot electron emission at 4.2 K. The experimental dependence I(H) coincides with the calculated magnetic field dependence of the exchange scattering cross-section of Cr⁺ ion with the spin 5/2 and g-factor 2. This result also indicates that both the Coulomb interaction with Cr+ ions and the exchange scattering on them present during the hot electron emission in the ZnS:Cr TFELS.